Daya Hambat Ekstrak Biji Kopi Robusta (Coffea Canephora) terhadap Bakteri Porphyromonas gingivalis (in vitro) - Rr. Nektara Titan Dianastri; Pudji Astuti; Rendra Chriestedy Prasetya (Fakultas Kedokteran Gigi Universitas Jember, 2021)
Periodontitis is mostly caused by plaque and Pophyromonas gingivalis bacteria as the main cause. The outer membrane layer of the Porphyromonas gingivalis wall produces pathogenic virulence factors, such as lipopolysaccharides which will activate inflammatory cells and cause phagocytosis of antigens thereby triggering free radicals. Robusta coffee beans naturally contain caffeine, phenolic compounds, trigonellin, and chlorogenic acids as antibacterial and anti-inflammatory. The purpose of this study was to determine the inhibition of Robusta (Coffea canephora) coffee bean extract 0.5%; 0.75%; 1%; 1.25%; 1.5% and 3% on the growth of Porphyromonas gingivalis in vitro and to find out the lowest concentration of Robusta (Coffea canephora) coffee bean extract which has inhibitory effect on the growth of Porphyromonas gingivalis. In this study were divided into 8 treatment groups namely positive control, negative control, 0.5% robusta coffee bean extract, 0.75%, 1%, 1.25%, 1.5% and 3%. Petridish dishes containing TSA media that have been sterilized, added P. gingivalis suspension with density according to Mc standard. Farland Then a sterile white test blank with a diameter of 6 mm that is still sterile is placed on top of the bacterial growth media in accordance with the placement of the treatment group and dropped with all 8 treatment materials. After 24 hours incubated in a desiccator, the inhibition of robusta coffee bean extracts against the growth of Porphyromonas gingivalis bacteria was observed and data collection was done by measuring the inhibition zone using calipers. The results obtained robusta coffee bean extract at concentrations of 3%, 1.5%, 1.25% and 1%, have an antibacterial power which is suspected because Robusta coffee beans naturally contain ingredients such as caffeine, polyphenols and chlorogenic acids which have antibacterial activity while the robusta coffee bean extract with a concentration of 0.5% and 0.75% does not have antibacterial power against Pophyromonas gingivalis. Robusta coffee bean extract with a concentration of 1% is the smallest concentration of Robusta (Coffea canephora) coffee bean extract which can inhibit the growth of Porphyromonas gingivalis.